Identification of XylR, the Activator of Arabinose/Xylose Inducible Regulon in Sulfolobus acidocaldarius and Its Application for Homologous Protein Expression - van der Kolk, Nienke; Wagner, Alexander; Wagner, Michaela; Waßmer, Bianca; Siebers, Bettina; Albers, Sonja-Verena (Frontiers in Microbiology, 2020)
The thermophilic archaeon Sulfolobus acidocaldarius can use different carbon sources for growth, including the pentoses D-xylose and L-arabinose. In this study, we identified the activator XylR (saci_2116) responsible for the transcriptional regulation of the pentose transporter and pentose metabolizing genes in S. acidocaldarius. A xylR deletion mutant showed growth retardation on D-xylose/L-arabinose containing media and the lack of transcription of the respective ABC transporter. In contrast to so far used promoters for expression in S. acidocaldarius, the xylR responsive promoters have a very low background activity. Finally, two XylR dependent promoters next to the long-established maltose inducible promotor were used to construct a high-throughput expression vector system for S. acidocaldarius to efficiently clone and express proteins in S. acidocaldarius.